An Analysis of the Fishing Industry in Namibia: The Structure, Performance, Challenges, and Prospects for Growth and Diversification - Chiripanhura, Blessing; Teweldemedhin, Mogos (International Food Policy Research Institute, 2016)
This paper analyses the structure of Namibia’s fishery sector, which consists of both marine-based fisheries and aquaculture. The study examines the sectors’ governance structure and the evolution of fishery stocks and assesses the performance of the sector in terms of catch effort, sectoral contribution to GDP, employment, and contribution to international trade. The analysis concentrates on the marine-based fisheries and applies two analytical methods: a qualitative approach that solicits views from local fishing associations and companies and a quantitative approach that uses the decision support model to identify realistic export opportunities. The main challenges inhibiting the growth of Namibia’s fishery sector include a shortage of skilled labor, a lack of vessels, seismic impacts of oil exploration, and threats posed by proposed phosphate mining at sea. The paper also examines the government’s drive for value addition, arguing that what is deemed value addition from one angle may constitute value destruction from another. The authors also argue that the drive for value addition may cause companies to face problems with their current trading partners, who may use sanitary and phytosanitary measures to restrict the entry of processed fish into their markets.